1995
DOI: 10.1073/pnas.92.5.1337
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor protects against experimental lethal Escherichia coli septic shock in mice.

Abstract: Leukemia inhibitory factor (LIF) has recently been associated with septic shock in humans. In this study we sought to determine, in mice, the role of LIF in septic shock During sublethal endotoxemia, serum LIF levels, as determined by radio-receptor competition assay, peaked at 2 h and were low (3 ng/ml), whereas in lethal Escherichia coli septic shock serum LIF levels rose progressively (>30 ng/ml) in the premorbid phase coincident with the development of tissue injury. Single i.v. injections of high doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…15 This interpretation would be coherent with our results, which are consistent with the data showing that an injection of LIF prior to LPS protected the mice from endotoxic shock. 11 Furthermore, we were able to attenuate LPS toxicity in LIFÀ/À mice by exogenous LIF.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…15 This interpretation would be coherent with our results, which are consistent with the data showing that an injection of LIF prior to LPS protected the mice from endotoxic shock. 11 Furthermore, we were able to attenuate LPS toxicity in LIFÀ/À mice by exogenous LIF.…”
Section: Discussionmentioning
confidence: 80%
“…dose of LIF is able to protect mice from the lethal effect of LPS 12 and live E. coli. 11 The protection by prior administration of LIF does not necessarily have to be the same mechanism as the observed sensitization in the absence of LIF. It has been suggested that induction of the APP plays a central role in establishing protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that LIF is one of the principal agents in the lethality associated with septic shock. Surprisingly, LIF injection prior to a challenge with a high dose of LPS protects against the lethal effects of endotoxin [96,97], suggesting that LIF may also exert anti-inflammatory activities. Similarly, intratracheal coinjection of LIF and LPS inhibits the acute inflammatory response that is usually triggered by LPS alone [98].…”
Section: Lif In Acute and Chronic Inflammationmentioning
confidence: 99%
“…Further, LIF was increased as a potent pro-inflammatory cytokine in sepsis (7,8), arthritis (9,10), injury (11) and dermatitis (12). Prior administration of high dose LIF protects from lethality in E. coli-induced septic shock (13). LPS induces 10-fold higher TNF-· and IL-6 serum level and reduces IL-10 production in LIF deficient mice (7).…”
Section: Introductionmentioning
confidence: 99%